Respuesta :

Recall that for all [tex]z\in\Bbb C[/tex],

[tex]\sin(z) = \dfrac{e^{iz} - e^{-iz}}{2i}[/tex]

so that

[tex]\sin(z) = a \iff e^{iz} - e^{-iz} = 2ia[/tex]

Multiply both sides by [tex]e^{iz}[/tex] to get a quadratic equation,

[tex]e^{2iz} - 2iae^{iz} - 1 = 0[/tex]

Solve for [tex]e^{iz}[/tex]. By completing the square,

[tex]e^{2iz} - 2ia e^{iz} + i^2a^2 = 1 + i^2a^2[/tex]

[tex]\left(e^{iz} - ia\right)^2 = 1 - a^2[/tex]

[tex]e^{iz} - ia = \pm \sqrt{1-a^2}[/tex]

[tex]e^{iz} = ia \pm \sqrt{1-a^2}[/tex]

[tex]iz = \log\left(ia \pm \sqrt{1-a^2}\right)[/tex]

[tex]iz = \ln\left|ia \pm \sqrt{1-a^2}\right| + i \left(\arg\left(ia \pm \sqrt{1-a^2}\right) + 2\pi n\right)[/tex]

[tex]\boxed{z = -i \ln\left|ia \pm \sqrt{1-a^2}\right| + \arg\left(ia \pm \sqrt{1-a^2}\right) + 2\pi n}[/tex]

where n is any integer.

We are given with:

[tex]{\quad \qquad \longrightarrow \sin (z)={\sf a}\:,\:z\in \mathbb{C}}[/tex]

Recall the identity what we have for the sine function of complex numbers

  • [tex]{\boxed{\bf{\sin (z)=\dfrac{e^{\iota z}-e^{-\iota z}}{2\iota}}}}[/tex]

Put the values to thus obtain:

[tex]{:\implies \quad \sf \dfrac{e^{\iota z}-e^{-\iota z}}{2\iota}=a}[/tex]

[tex]{:\implies \quad \sf e^{\iota z}-e^{-\iota z}=2a\iota}[/tex]

Multiply both sides by [tex]{\sf e^{\iota z}}[/tex]

[tex]{:\implies \quad \sf e^{\iota z}\cdot e^{\iota z}-e^{-\iota z}\cdot e^{\iota z}=2a\iota e^{\iota z}}[/tex]

[tex]{:\implies \quad \sf (e^{\iota z})^{2}-2a\iota e^{\iota z}-1=0}[/tex]

Put x = [tex]{\sf e^{\iota z}}[/tex]:

[tex]{:\implies \quad \sf x^{2}-2a\iota x-1=0}[/tex]

Find the discriminant, here D will be, D = (-2ai)² - 4 × 1 × (-1) = 4 - 4a² = 4(1-a²)

Now, By quadratic formula:

[tex]{:\implies \quad \sf x=\dfrac{-(-2a\iota)\pm \sqrt{4(1-a^{2})}}{2}}[/tex]

[tex]{:\implies \quad \sf x=\dfrac{a\iota \pm \sqrt{1-a^{2}}}{2}}[/tex]

[tex]{:\implies \quad \sf e^{\iota z}=\dfrac{a\iota \pm \sqrt{1-a^{2}}}{2}}[/tex]

[tex]{:\implies \quad \sf \iota z=log\bigg(\dfrac{a\iota \pm \sqrt{1-a^{2}}}{2}\bigg)}[/tex]

Using the formula for logarithms, we have:

[tex]{:\implies \quad \sf \iota z=log(a\iota \pm \sqrt{1-a^{2}})-log(2)}[/tex]

[tex]{:\implies \quad \sf z=\dfrac{1}{\iota}log(a\iota \pm \sqrt{1-a^{2}})-\dfrac{1}{\iota}log(2)}[/tex]

The sine function is periodic on 2πn and zero on (π/2), and the logarithmic expression becomes undefined for all ia±√(1-a²) < 0, so we will take modulus of it

[tex]{:\implies \quad \boxed{\bf{z=\dfrac{1}{\iota}log\bigg|a\iota \pm \sqrt{1-a^{2}}\bigg|-\dfrac{1}{\iota}log(2)+\dfrac{\pi}{2}+2\pi n\:\:\forall \:n\in \mathbb{Z}}}}[/tex]